Flash spark plasma sintering of HfB2 ceramics without pre-sintering. (November 2018) - Zou, Ji; Grasso, Salvatore; Liu, Lei-Feng; Ma, Hai-Bin; Reece, Mike; Binner, Jon
Abstract: Strong HfB2 powder green bodies with compressive strengths exceeding 20 MPa have been produced by incorporating 1 wt% of glassy carbon derived from a pyrolyzed phenolic resin binder. Starting from the green body after debinding in argon, non-textured HfB2 ceramics (diameter ~ 20 mm and height ~ 4 mm) with a relative density of 95.1% were achieved using flash spark plasma sintering (FSPS) with a discharge time of 20 s, peak power of 19 kW and applied pressure of ~16 MPa. The lack of a need for a pre-sintering step resulted in energy savings compared to the densification of HfB2 ceramics by FSPS. Graphical abstract: Unlabelled Image